Resistance Rates of Mycobacterium tuberculosis Complex Isolates to Primary Anti-tuberculosis Drugs: A 5-Year Retrospective Study - Sondos A. A. Ibnouf; Fatma Esenkaya Taşbent (Genel Tıp Dergisi)
Background/Aim: Tuberculosis remains a major global health problem with a high morbidity and mortality rate, approximately a quarter of the population is infected with tuberculosis. Drug susceptibility testing is an essential tool for identifying and managing drug-resistant tuberculosis. This study was conducted to evaluate the drug susceptibility pattern of Mycobacterium tuberculosis complex strains isolated from a university hospital. Methods: A total of 10900 samples sent to the microbiology laboratory with the suspicion of tuberculosis clinically between January 2018 and January 2022 were analyzed retrospectively. The automated BACTEC MGIT 960 (Becton Dickinson, USA) was used for sample culture and susceptibility testing. The obtained data were statistically analyzed with the Statistical Package for Social Sciences (SPSS version 20). Results: Out of the 154 isolated positive samples, males and females constituted equal parts of the study population (50%). The majority of tuberculosis cases were in the age group 56–75 years (42.2%), Pulmonary TB was detected in (90.3%) of the patients, while extrapulmonary TB cases were observed in (9.7%). As a result of susceptibility studies on positive samples, isoniazid resistance was 5.2%; streptomycin resistance 1.3%; ethambutol resistance was detected at a rate of 0.6%, while no rifampicin resistant sample was found. Both streptomycin and isoniazid resistance were seen together in 1.3% of the samples. Conclusion: A similar resistance pattern of the first-line antituberculosis drugs was observed in other studies conducted in different provinces of Turkey. The absence of multi-drug resistant and extensively drug-resistant tuberculosis in our study indicates that the tuberculosis surveillance program implemented in our region was successful.